Equivalent living conditions and sectoral policy – explorative observations and deliberations illustrated using the example of the current coal policy - Mäding, Heinrich (Raumforschung und Raumordnung | Spatial Research and Planning, 2022)
This paper opens with a sketch of the general spatial policy objective: ‘Equivalent living conditions’ before exploring the significance of this objective in the context of current legislation on coal policy. Based on the most relevant documents (ranging from the report of the coal commission in January 2019 to the protocol of the final plenary sessions of both houses of the German federal parliament in July 2020), the operationalisation and importance accorded to the equivalence objective are traced. Despite the great relevance of coal policy for equivalent living conditions and the postulated relevance of equivalence for the coal policy, the connections remain ill-defined, usually implicit and insufficiently comprehensible. In the political process equivalence is becoming much less significant than arguments related to climate and energy policy.
Keywords: Equivalence; Sectoral policy; Coal policy; Climate protection policy; Structural development Act; Coal Phase-out Act